KÓPLIKLER TEORIYASÍ TÚSINIGI ARQALÍ OQÍWSHÍLARDÍŃ KREATIVLILIGIN PAYDA ETIW - Tanirbergenov, S.A.; Berdieva, Z.İ. (SCIENCE and SOCIETY, 2021)
According to the concept of the multitudes of articles, it was looked through the work of improving the pupils’ creative. Here primary and senior grades, it was looked through, during math lessons thought of multitudes how to teach pupils with the help of style of examples.